The Developing of Creative Thinking Skills Test Based on Modern Test Theory in Physics of Senior High Schools - Edi Istiyono; Wipsar Brams Dwandaru; Farida Rahayu (Jurnal Cakrawala Pendidikan, 2018)
Abstract: In general, a test was developed based on classical test theory which had many weaknesses, therefore the test in this research was developed based on modern test theory (Item Response Theory). This study aimed to develop a Creative Thinking Skills test on physics lessons for Class X High School (PhysCreTHOTS) that eligible to be used based on modern test theory. This research was a development research using 4D model which involving 300 students of Class X High School in Gunung Kidul District of DIY. The scoring of test items using four categories of politomus scales and Partial Credit Model (PCM) techniques. The characteristics of the test consist of item match, reliability, difficulty level of item, information function and Standard Error of Measurement (SEM). The results showed that the instrument's reliability was 0.72. The entire test instrument is considered fit with PCM, with an INFIT MNSQ range of 0.93 to 1.10. The difficulty index of 63 items ranges from -1.06 to 1.04. Based on the information function and SEM it is known that the test instrument corresponds to the learner with a score of -1.8 to 3.0. The entire test is considered feasible to be used to measure Creative Thinking Skills in Physics lessons for high school X grade students.Keyword: creative thinking skills, partial credit model, polytomus, physics Pengembangan Tes Creative Thinking Skills Fisika SMA (Physcrethots)  Berdasarkan Teori Tes ModernAbstrak: Pada umumnya tes dikembangkan berdasarkan teori tes klasik yang banyak kelemahannya, maka tes yang dikembangkan ini dilakukan berdasarkan teori tes modern (Item Rseponse Theory). Penelitian bertujuan untuk mengembangkan tes Creative Thinking Skills fisika Kelas X SMA (PhysCreTHOTS)  yang layak digunakan berdasarkan teori tes modern. Penelitian ini merupakan penelitian pengembangan menggunakan model 4D yang melibatkan 300 peserta didik Kelas X SMA di Kabupaten Gunung Kidul DIY. Penskoran item tes menggunakan skala politomus empat kategori dan menggunakan teknik Partial Credit Model (PCM). Karakteristik tes terdiri atas kecocokan item, reliabilitas, tingkat kesukaran item dan fungsi informasi dan Standard Error of Measurement (SEM). Hasil penelitian menyatakan bahwa realiabilitas instrumen sebesar 0,72. Keseluruhan instrumen tes dinyatakan fit dengan PCM, dengan rentang INFIT MNSQ 0,93 sampai 1,10. Indeks kesukaran 63 item (difficulty) antara -1,06 sampai 1,04. Berdasarkan fungsi informasi dan SEM diketahui bahwa instrumen tes sesuai dengan peserta didik berkemampuan dari -1,8 sampai 3,0. Keseluruhan tes dinyatakan layak digunakan untuk mengukur Creative Thinking Skills Fisika peserta didik kelas X SMA.Kata kunci : creative thinking skills, partial credit model, politomus, fisika